Book Publishing in Barnaul in the Pre-Revolutionary Period - J. V. Timofeeva (Библиосфера)
The social significance of book publishing is determined by the large role of print media in personal education, in the dissemination of knowledge and ideas. Therefore, the study of this sociocultural phenomenon is an important area of modern scientific research. The purpose of this article is to make a quantitative analysis of book publishing in Barnaul in the pre-revolutionary period. The quantitative indicators of book publishing in Barnaul town per year and in general for the pre-revolutionary period were calculated. The results obtained showed that from the XIX century to 1917 at least 210 titles were issued in Barnaul, with the exception of periodic ones. The most productive were 1899 and 1900, when 13 titles were issued in each. Printing houses that worked in the town in the pre-revolutionary period were identified. The share of each of them was determined by the number of titles printed in it. Thelargest part – 44.8 % – was published in the Main Directorate of the Altai Mining District. The publishing repertoire and the author’s corps were outlined. The latter was represented mainly by persons who worked in Altai District. Many authors were the members of the Society of lovers of Altai exploration. The main group of publishers was formed by local societies, that’s why their office documentation was a noticeable part of printed materials and determined the publishing repertoire of Barnaul printing houses.